Evaluation of the power of movements of rowers-canoeists based on the spatial reconstruction of the stroke - Sushchenko, V. P.; Vasyuk, V. E.; Lukashevich, D. A.; Huseynov, D. I.; Pashuta, V. L. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the biomechanical characteristics of rowing and their relationships in the "oar-water-boat" system. Show new methods for quantifying movement technique in canoeing.